ASSESSMENTS OF THE DETERMINANTS OF INVESTMENT ACTIVITIES IN NEKEMTE TOWN - Gofe, Tesfaye Eresso (International Journal of Research -GRANTHAALAYAH, 2018)
Investment activity plays a crucial role in the economic growth of a country. Economic literatures show that investment is, both empirically and theoretically, the key determinant to economic growth. Investment can increase a country’s productive capacity, provided that investment expenditure regards durable goods that have comparatively long useful lives and embody the latest technological advances. Economic growth refers to an increase in a country’s production or income per capita. The study assessed the determinants of investment activities in Nekemte town which is found in Oromia region with 328km away from Addis Ababa the capital city of Ethiopia. The research was investigated the major determinants of investment activities in the town and indicates the direction for investment how to deal with those determinants. For this study both primary and secondary data were used. Because of the heterogeneity of the activities the researcher was used stratified sampling techniques and the sample size was computed using solvin’s formula. In this research the descriptive analysis was employed. Some of the main findings of the study were difficulties of finance and lack of credits when they started their business, and low encouragement from the investment offices are the major findings of this study. Finally, investment related problem is not the responsibility of the government alone, but also all investors, the local community, the private business man of the town has to work together with the government so as to attain the desired objectives.